Managing Human Resources During a Global Crisis: A Multilevel Perspective. (15th February 2023) - Malik, Ashish; Sanders, Karin
Abstract: We develop a multi‐level framework for understanding the impact of human resource management (HRM) practices in managing people during a significant global crisis. We provide a critical review of the research on the topic, focusing on papers published in the British Journal of Management (BJM). Our review focuses on papers dealing with people management issues during or after a global crisis event. To this end, two BJM special issues and other articles on global crises published were selected for our critical review. Our choice of additional papers reviewed was deliberate. We reviewed papers from several other premier outlets covering diverse geographies. Such an approach allows for delineating critical factors and practices that stand out despite national, cultural, industry and sectoral differences. These papers cover the two major global crises in the last two decades: the Global Financial Crisis and the COVID‐19 Pandemic. We conclude with future research directions.